The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1371/journal.pone.0213019
|View full text |Cite
|
Sign up to set email alerts
|

Respective roles of migration and social deprivation for virological non-suppression in HIV-infected adults on antiretroviral therapy in France

Abstract: Barriers to achieve sustained HIV virological suppression on antiretroviral therapy (ART) jeopardize the success of the 90:90:90 UNAIDS initiative which aims to end the HIV/AIDS epidemic. In France, where access to ART is free and universally available, we analyze the way in which social determinants of health (i.e. cultural, environmental) and economic factors might influence virological outcomes. A cross-sectional study was performed in two hospitals located in Paris area. All consecutive people living with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 24 publications
(29 reference statements)
0
13
0
Order By: Relevance
“…Detectable VL was more common among ART recipients in the United Kingdom with unstable housing, non-university education, unemployment and financial hardship [15]. Other social and structural factors, such as homelessness, injection drug use and lack of social support, have also been associated with viremia during ART [16,17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Detectable VL was more common among ART recipients in the United Kingdom with unstable housing, non-university education, unemployment and financial hardship [15]. Other social and structural factors, such as homelessness, injection drug use and lack of social support, have also been associated with viremia during ART [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Lack of virological suppression during ART has been associated with advanced immunosuppression, high baseline viral load, longer ART duration, younger age and male gender [8][9][10][11][12][13]. Failure to achieve virological suppression has also been linked to various socio-demographic factors, including unstable housing, low educational status, unemployment and lack of financial or social support [14][15][16][17]. These factors have been associated with disease outcomes in a range of both communicable and non-communicable conditions, and are considered as important determinants of health [18].…”
Section: Introductionmentioning
confidence: 99%
“…Poverty and deprivation are reported as fundamentally neighbourhood or area level factors and based on contextspecific measurement tools, including the Evaluation of Deprivation and Inequalities in Health Examination Centres (EPICES). Two of nine studies reported a significant adjusted negative association with virological suppression and deprivation [95,115]. For instance, Raho-Moussa et al [115] found that individuals who reported either individual determinants of deprivation (specifically financial difficulties in past month) or had an EPICES score indicating residence in a deprived state were 66% (aOR 0.34; 95% CI 0.16, 0.72) and 65% (aOR 0.35; 95% CI 0.14, 0.85) less likely, respectively, to achieve a VL < 50 copies/mL, compared to people living with HIV who did not meet these measures of deprivation, after adjusting for age and medication-, and clinically-related factors.…”
Section: Poverty and Deprivationmentioning
confidence: 99%
“…Two of nine studies reported a significant adjusted negative association with virological suppression and deprivation [95,115]. For instance, Raho-Moussa et al [115] found that individuals who reported either individual determinants of deprivation (specifically financial difficulties in past month) or had an EPICES score indicating residence in a deprived state were 66% (aOR 0.34; 95% CI 0.16, 0.72) and 65% (aOR 0.35; 95% CI 0.14, 0.85) less likely, respectively, to achieve a VL < 50 copies/mL, compared to people living with HIV who did not meet these measures of deprivation, after adjusting for age and medication-, and clinically-related factors. Only one study reported a significant adjusted association with medication adherence which was in a negative direction [63].…”
Section: Poverty and Deprivationmentioning
confidence: 99%
“…Migrant people or people with social vulnerability respond less well to ART. 35 A survey analysing the Bichat hospital's HIV care unit database in 2015 showed that transgender people were more exposed to HIV and other sexually transmitted infections (STI) than other populations, and that their dermatological complications needed better management. 36 A second survey in the same care unit, which aimed to highlight the dangers associated with the clandestine use of cosmetic surgery, reinforced these results and showed that transgender women also presented physical health risks related to the illicit use of silicone.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%